Job Evaluation and Wage Setting in the Public Sector of Israël - Harel, Gedaliahu (Relations industrielles / Industrial Relations, 1976)
This paper examines the Israeli experience with spectoral job evaluation and incomes policy analysis, and the causes for the abortive attempt.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Generic Reasons for Strikes: An Interpretative Analysis of the Israëli Case - Blum, Albert A.; Harel, Gedaliahu H. (Relations Industrielles / Industrial Relations, 1980)
The purpose of this paper is to reveal those universal socioeconomic conditions which generally foster strikes, and the most general labor relations-related reasons for conflicts which eventually resuit in strikes.

Winners and Losers: A Multivariate Content Analysis of Israel's Tribunal for Voluntary Arbitration - Kirschenbaum, Alan; Harel, Gedaliahu; Sivan, Niza (Relations industrielles / Industrial Relations, 1998)
The objective of this paper is to examine the arbitration process instituted in arbitration tribunals and propose a parsimonious model to enhance the predictive ability of theoretical factors affecting the outcome of public sector labor disputes. The basic data set was generated by a content analysis of 101 awards made by Israel's Tribunal for Voluntary Arbitration during its first 8 years of operation (1977-1984). Results are discussed within the context of employee groups choosing arbitration over strikes as a means of winning demands.
Keywords: Arbitration; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Labor relations; Models; Public sector; Regression analysis; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies